2007
DOI: 10.1253/circj.71.968
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Body Mass Index and Leucopenia After Administration of Valganciclovir for Cytomegalovirus Infection in Chinese Cardiac Recipients

Abstract: ytomegalovirus (CMV) infection is an importantcomplication after solid organ transplantation. It is believed that more than 50% of transplant recipients are affected by this troublesome complication, which causes graft failure and mortality if the infection is not treated promptly. 1 The risk factors include CMV-seronegative recipients who receive organs from CMV-seropositive donors or CMV-seropositive recipients who received anti-Tcell antibodies, such as anti-thymocyte globulin or muromonab-CD3 (Orthoclone O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…12,13 It is noteworthy that higher incidences of leukopenia and/or neutropenia have been found in studies involving a small number of patients, probably causing some bias. 12,13 In contrast to our study, Rerolle et al 12 observed severe infectious complications associated with neutropenia. The difference from our patients may result from the intensive monitoring, and prompt use of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 It is noteworthy that higher incidences of leukopenia and/or neutropenia have been found in studies involving a small number of patients, probably causing some bias. 12,13 In contrast to our study, Rerolle et al 12 observed severe infectious complications associated with neutropenia. The difference from our patients may result from the intensive monitoring, and prompt use of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only one study that looked at risk factors associated with VGC-induced leukopenia. 13 Chen et al 13 demonstrated that VGC toxicity was related to low body mass index, suggesting that dose should be adjusted to body weight, as racial or genetic factors may be important.…”
Section: Discussionmentioning
confidence: 99%
“…When the renal function is decreased, the half-life of the drug can increase up to 13 times. It has not been reported to MMF itself cause bone marrow toxicity with such severity; however, in cases of aplastic anemia induced by valganciclovir (confirmed by biopsy) it has been observed increase in serum free fraction of MMF, which could explain the synergistic effect for the development of leucopenia [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective analysis by Brum, et al searching for risk factors for the development of leucopenia, they found that the use of valganciclovir and MMF, the origin of the graft (higher risk in deceased donor) and the start of the prophylaxis in the first post transplant day were the most related factors [6,7]. The main side effect of valganciclovir is leucopenia, which occurs in 10-55% and atinine 1.0 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…Transplant recipients are known to develop neutropenia frequently, especially in the early posttransplant period, with incidence reported at 4.9% and 37.5% in two studies [4,5]. Although the etiology of neutropenia is often multifactorial (viral or other systemic infection, malignancy including posttransplant lymphoproliferative disorders, etc.…”
Section: Discussionmentioning
confidence: 99%